Gambaran Pelayanan Informasi Obat Terhadap Pasien Rawat Jalan Di Instalasi Farmasi Rumah Sakit Umum Imelda Pekerja Indonesia Medan - Mutiara Siahaan (The Journal General Health and Pharmaceutical Sciences Research, 2023)
Drug information services were activities that carried out by pharmacists to provide information about drugs that is impartial, critically evaluated, and with the best evidence in all aspects of drug use to other health professionals, patients, or the public. Providing drug information has an important role in improving the quality of life of patients and providing quality services for them. The purpose of this study was to determine drug information services for outpatients in the pharmaceutical installation of Imelda Pekerja Indonesia Public Hospital. This study used qualitative research methods with a sample of pharmaceutical officers who provided drug information services to outpatients, as many as 100 patients. Data collection was carried out by interview, direct observation, and using a check list sheet of drug information components. The results showed that the percentage of components conveyed when delivering drug information, including the name of the drug, drug dosage, type of preparation, rules of use, how to use, time of use, amount of drug, and efficacy or indications, had a percentage of 100%. While the drug information component that is rarely conveyed is how to store the drug with a percentage of 8%, the drug information component that is not conveyed is the side effects of the drug. The results of this study indicate that drug information services to outpatients carried out by pharmaceutical officers in the pharmaceutical installation of the Imelda Pekerja Indonesia Medan Public Hospital have been well implemented, with a percentage of 80.80%. The results also concluded that the drug information services carried out by the pharmacist of Imelda Pekerja Indonesia Public Hospital, Medan, were in accordance with hospital procedures and Regulation of the Minister of Health of the Republic of Indonesia Number 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals.